Perspektif Hukum Islam dalam Menanggapi Fenomena Mahar Unik di Indonesia - Luthfia, Chaula (INTERDISCIPLINARY JOURNAL ON LAW, SOCIAL SCIENCES AND HUMANITIES, 2024)
According to Islamic marriage contracts, dowry is the husband's obligation and the wife's right. Dowry is a form of respect for women in Islam, which glorifies them by giving them the right to own property. Giving dowry is done in ways that are considered different, impressive, and unique. For example, current trend of giving dowry within the community include setting the amount of dowry with a unique nominal, framing the dowry in certain forms, and giving dowry with unique items. Here, a problem arises with how Islamic Law sees the phenomenon of these unique dowry trends. This research employs library methods, utilizing a normative and philosophical approach. The result of this research is that Islam does not determine the amount of dowry, nor what type or form it should be. Marriage can be achieved even with a simple dowry, as long as it is useful, has value, is sacred and not haram, is tradeable and can raise the wife's prestige. A dowry of a unique item or object is permissible, and the dowry can be simple, if it can benefit the prospective couple.Keywords: Dowry Substance, Unique Dowry Trend, Wedding.